2012
DOI: 10.1586/erc.12.91
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban for stroke prevention in atrial fibrillation: a critical review of the ROCKET AF trial

Abstract: Oral anticoagulation is the mainstay of therapy for stroke prevention in patients with atrial fibrillation (AF). Vitamin K antagonists such as warfarin have many drawbacks that reduce their uptake, safety and effectiveness. The ROCKET AF trial compared rivaroxaban (20 mg/day; 15 mg/day in patients with creatinine clearance 30-49 ml/min) with dose-adjusted warfarin (international normalized ratio 2-3) in 14,264 patients with AF and a prior history of stroke or at least two other additional risk factors for stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Rivaroxaban has also been shown to reduce the rate of death, myocardial infarction, or stroke in patients with acute coronary disease and is not inferior to warfarin as an anticoagulant for these patients . Studies have also shown that its use results in a similar bleeding rate as wafarin, with a reduction in the risk of intracranial bleeding but an increase in risk of GI bleeding . Rebound hypercoagulability has been reported if the medication is abruptly stopped in human patients, and replacement with a different anticoagulant is recommended in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rivaroxaban has also been shown to reduce the rate of death, myocardial infarction, or stroke in patients with acute coronary disease and is not inferior to warfarin as an anticoagulant for these patients . Studies have also shown that its use results in a similar bleeding rate as wafarin, with a reduction in the risk of intracranial bleeding but an increase in risk of GI bleeding . Rebound hypercoagulability has been reported if the medication is abruptly stopped in human patients, and replacement with a different anticoagulant is recommended in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, these medications are not as well known or well studied in veterinary patients. Rivaroxaban is a direct factor Xa anticoagulant newly approved in human patients for treatment or prevention of arterial or venous thrombosis . To the authors’ knowledge, there are no reported cases of the clinical use of rivaroxaban in dogs with thromboembolic disease.…”
Section: Introductionmentioning
confidence: 97%
“…In this way it emphasizes the important barrier concerning warfarin. Therefore, novel anticoagulants will be welcomed in real world practice against stroke prevention in patients with AF [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…An individual with this condition is 5 times more likely to suffer a stroke than a person who lacks this condition. 4 The chance of men and women over the age of 40 developing AF is 25%. 2 Historically, vitamin K antagonists (VKAs) such as warfarin (Coumadin) have formed the backbone of anticoagulant therapies for treatment of thromboembolic disease and cardiac arrhythmias.…”
mentioning
confidence: 99%
“…Despite these advantages, many providers continue to use VKAs for long term management because they have little clinical experience with DOACs and VKAs have represented the gold standard for thromboembolic therapy for a long time. 1 VKA = vitamin K antagonist; DOAC = direct oral anticoagulant Figure adapted from (1,4) open access. F Fi ig gu ur re e 1 1. .…”
mentioning
confidence: 99%